Periodicity of Elections in International Human Rights and Periodicity in Velayate Faqih in Emamieh Jurisprudence - eyyed Qasem Zamani; mohamad adami (پژوهش تطبیقی حقوق اسلام و غرب, 2016)
According to international and regional documents, the right to political participation, and in particular periodic elections, are considered as human rights. Right to periodical election is considered as a negative right and produces obligations of results or obligations of immediate results right. The right to elections and its periodicity has a serious relationship with the right to self-determination and it is a branch of it. This right may be limited or suspended under certain conditions.The issue of Periodicity of Velayat-e Faqih has been less elaborated in the Imamieh jurisprudence.  The few discussions that have taken place around the periodicity, are more focused on social issues and do not have the precise jurisprudential examination. The result of this article is that the periodicity of Velayat-e Faqih is not in opposition to the Islamic holy religion. This is based on some reasons like “Moghadamate Hekmat”, “Principle of Establishment of the Islamic State”, “Principle of maintaining the Islamic system”. Of course, social, cultural, municipal, international and security interests and circumstances should be considered for making decision about the periodicity of Velayat Faqih, in practice, and preliminary allowance in Fiqh would not be enough.